STUDENTS’ PERCEPTION ON THE USE OF COOPERATIVE LEARNING IN EFL LEARNERS - Dawi Yanti (Universitas Muhammadiyah Kalimantan Timur, 2020)
ABSTRACT This paper reports a case study aimed at observing the perception of 24 learners in Teknik Instrumentasi Electronika Migas at STT-Migas Balikpapan on the use of cooperative learning. The instruments used were a questionnaire and the analysis showed that the participant generally learning experiences contribute to social skills growth, where positive interpersonal and social relationship became to noticeable and more diverse. Through cooperative learning, individual and group work skills development enhances students' achievement. Keywords: students perception, cooperative learning